2008
DOI: 10.1242/jcs.000455
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin switching

Abstract: occurs during normal developmental processes to allow cell types to segregate from one another. Tumor cells often recapitulate this activity and the result is an aggressive tumor cell that gains the ability to leave the site of the tumor and metastasize. At present, we understand some of the mechanisms that promote cadherin switching and some of the pathways downstream of this process that influence cell behavior. Specific cadherin family members influence growthfactor-receptor signaling and Rho GTPases to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
738
3
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(778 citation statements)
references
References 127 publications
26
738
3
11
Order By: Relevance
“…Alteration in cell adhesion is a hallmark feature of metastasis (Wheelock et al, 2008). Earlier studies have documented the switching of cadherin profiles during ovarian tumor progression (Patel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration in cell adhesion is a hallmark feature of metastasis (Wheelock et al, 2008). Earlier studies have documented the switching of cadherin profiles during ovarian tumor progression (Patel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cadherins are a family of transmembrane glycoproteins that mediate Ca 2 þ -dependent homophilic cell-cell adhesion. Cadherin subtype switching in which other cadherins replace or are co-expressed with E-cadherin during embryogenesis has important functional roles in cell segregation (Wheelock et al, 2008). Tumor cells often recapitulate this activity during cancer progression in which tumor cells acquire the capacity to migrate, invade, and metastasize.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, biophysical studies demonstrated that E-cadherin mediates stronger bonds at the molecular level than any other cadherins (Dufour et al, 1999;Chu et al, 2006;Panorchan et al, 2006). Moreover, although E-cadherin and N-cadherin may transiently coexist in certain cells, they are generally mutually exclusive, and studies on epithelial cell lines or in mouse and Xenopus embryos in which E-and N-cadherins have been interchanged clearly indicate that they can only partially substitute each other (Luo et al, 2001;Kan et al, 2007;Wheelock et al, 2008;Nandadasa et al, 2009;Libusova et al, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…In particular, the switch between E-and N-cadherin has been found to play a key role in early morphogenesis and in pathological situations, by promoting the process of epithelium-to-mesenchyme transition (EMT; Wheelock et al, 2008;Thiery et al, 2009). During gastrulation, for example, N-cadherin is up-regulated at the expense of E-cadherin on the surface of nascent mesodermal cells ingressing from the superficial ectoderm into the primitive streak (Ohta et al, 2007;Nakaya et al, 2008;Hardy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…see Christofori 2003;Cavallaro & Christofori 2004;Yilmaz & Christofori 2009). Recent focus has been paid to a "cadherin switch" (Wheelock et al 2008), in which loss of E-cadherin is further accompanied by gain in the mesenchymal CAM N-cadherin, and the cell subsequently loses its affinity for its epithelial neighbours.…”
Section: For a Recentmentioning
confidence: 99%